EXPLORING THE LANGUAGE CHOICE OF THE NON-COMMERCIAL SIGNS IN JAKARTA - Silva, Anna Marietta da (Indonesian Journal of Applied Linguistics, 2017)
This article focuses on non-commercial signs in the linguistic landscape of Jakarta. Five main streets within or nearby the centroid of Jakarta are selected. The prevalence of English and the use of English words in the non-commercial signs are examined. The data cover 47 non-commercial signs which are investigated from the perspective of place semiotics. Despite their small number, this category of sign, mainly those that belong to the Regulatory discourse, holds a legal power. The presence of the non-commercial signs signifies the power of the state and communicates vertical and horizontal relationships between the authority and the audience. The findings suggest that the Infrastructural discourse is mostly available and Indonesian is the dominant language. English is present to a certain extent, particularly with regard to content related to technology and English prestigious status. Semantically, few English words had meaning extension when used in Indonesian context. The language choice of the non-commercial signs indicates the exclusiveness of Jakarta linguistic landscape.